Spiral carbon nanotube / doped barium ferrite composite material and preparation method and application thereof

By preparing spiral carbon nanotubes/doped barium ferrite composite materials, the overlapping effect of its tube-sheet structure is used to form a mesh structure, which solves the existing material combination problem and achieves a stronger electromagnetic wave absorption effect.

CN119430155APending Publication Date: 2025-02-14ARMOR ACADEMY OF CHINESE PEOPLES LIBERATION ARMY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310942982.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing spiral carbon nanotubes and barium doped ferrite materials each have the disadvantages of strong skin effect and high mass density, and it is difficult to effectively combine to enhance the electromagnetic wave absorption characteristics.

Method used

By preparing helical carbon nanotubes/barium doped ferrite composite materials, acidified helical multi-wall carbon nanotubes and barium doped ferrite tube-sheet structures overlap each other to form a fluffy rich in microcavity and conductive networks Mesh structure regulates the electromagnetic characteristics of the material and enhances impedance matching performance.

Benefits of technology

Effective overlap and dispersion of spiral carbon nanotubes and doped barium ferrite is achieved, enhancing the electromagnetic wave absorption capacity of the material, broadening the effective absorption frequency band and reducing reflection loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430155A_ABST
    Figure CN119430155A_ABST
Patent Text Reader

Abstract

The invention provides a spiral carbon nanotube / doped barium ferrite composite material and a preparation method and application thereof, the spiral carbon nanotube / doped barium ferrite composite material is a fluffy net structure rich in microscopic cavities and conductive networks, and comprises doped barium ferrite and spiral multi-walled carbon nanotubes, the doped barium ferrite is a doped barium ferrite sheet formed by growing doped barium ferrite particles in a sheet shape, the spiral multi-walled carbon nanotubes are attached to the surfaces and gaps of the doped barium ferrite particles, and active sites of the spiral multi-walled carbon nanotubes are in lap joint with the doped barium ferrite. Further, the barium-doped ferrite sheet and the spiral multi-walled carbon nanotube are overlapped with each other in a tube-sheet structure. The helical carbon nanotube / doped barium ferrite composite material provided by the invention has a relatively large specific surface area, abundant multi-layer interfaces and excellent electromagnetic attenuation capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a spiral carbon nanotube / doped barium ferrite composite material and a preparation method and application thereof, belonging to the technical field of materials, in particular to the technical field of electromagnetic wave absorption materials. Background Art

[0002] With the development of electronic equipment and wireless information technology, electronic technology has been widely used in industry, commerce and other fields. While making people's lives more convenient, it has also generated a lot of electromagnetic radiation pollution. In the military field, with the rapid development of radar detection technology, electromagnetic waves are widely used in the reconnaissance and detection of military targets, seriously affecting the battlefield survival and penetration capability of military equipment. How to reduce the radar reflection echo signal of military targets, that is, to improve the absorption and attenuation ability of electromagnetic waves and enhance stealth performance, has become one of the key indicators for measuring the combat performance of weapons and equipment. Absorbing materials can convert electromagnetic wave energy into other energies such as heat energy through mechanisms such as electrical loss and magnetic loss, thereby reducing the radar reflection echo signal of military targets. Therefore, the design and preparation of absorbing materials has become an indispensable means to improve tactical penetration capability and equipment survivability in modern warfare beyond visual range.

[0003] As a chiral material, spiral multi-walled carbon nanotubes have high electron mobility, large specific surface area, multiple suspension sites, good frequency adaptability and electromagnetic tunability, and produce polytype dielectric polarization relaxation and multiple electromagnetic wave backscattering, which can achieve broadband radar absorption and can be used as a network framework for absorbing materials. Doped barium ferrite has attracted widespread attention from scientific researchers due to its large specific saturation magnetization, high magnetocrystalline anisotropy, good chemical stability, low production cost and electromagnetic tunability, and is suitable for absorbing electromagnetic waves in the GHz range. In addition, it can also achieve multiple magnetic resonances in different frequency bands. Ion doping can promote Fe 3+ Fe 2+ The transformation of electromagnetic parameters can be adjusted to generate new superexchange interactions, introduce dual magnetic resonance, increase dipole concentration, optimize impedance matching and electromagnetic loss characteristics, and further enhance the electromagnetic wave absorption characteristics of barium ferrite. However, the above two types of materials have the disadvantages of strong skin effect and high mass density.

[0004] Therefore, providing a novel spiral carbon nanotube / doped barium ferrite composite material and its preparation method and application has become a technical problem that needs to be solved urgently in the field. Summary of the invention

[0005] In order to solve the above shortcomings and deficiencies, an object of the present invention is to provide a spiral carbon nanotube / doped barium ferrite composite material. The spiral carbon nanotube / doped barium ferrite composite material provided by the present invention can realize the composite, good overlap and effective dispersion of the two materials of spiral carbon nanotubes and doped barium ferrite, can effectively regulate the electromagnetic properties of the material, enhance the impedance matching performance, construct the formation of an electromagnetic coupling network, have more exposed surfaces, enhance the ability of synergistic dielectric and magnetic losses, further broaden the effective absorption frequency band of the material and enhance the reflection loss.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned spiral carbon nanotube / doped barium ferrite composite material.

[0007] Another object of the present invention is to provide the above-mentioned spiral carbon nanotube / doped barium ferrite composite material as an absorbing material for use in military equipment stealth, electronic equipment anti-electromagnetic interference, medical radiation protection or aerospace.

[0008] In order to achieve the above objectives, on the one hand, the present invention provides a spiral carbon nanotube / doped barium ferrite composite material, wherein the spiral carbon nanotube / doped barium ferrite composite material is a fluffy mesh structure rich in microscopic cavities and conductive networks, that is, a loose, porous, lightweight and conductive mesh structure, including doped barium ferrite and spiral multi-walled carbon nanotubes, the doped barium ferrite is a doped barium ferrite sheet formed by the sheet-like growth of doped barium ferrite particles, the spiral multi-walled carbon nanotubes are attached to the surface and gaps of the doped barium ferrite particles, the active sites of the spiral multi-walled carbon nanotubes overlap with the doped barium ferrite, and then the doped barium ferrite sheets and the spiral multi-walled carbon nanotubes overlap with each other in a tube-sheet structure.

[0009] As a specific embodiment of the composite material described above in the present invention, the mass ratio of the spiral multi-walled carbon nanotubes to the doped barium ferrite is 1:10-1:20.

[0010] As a specific embodiment of the composite material described above in the present invention, the spiral multi-walled carbon nanotubes are acidified spiral multi-walled carbon nanotubes.

[0011] As a specific embodiment of the composite material described above, the doped barium ferrite includes BaFe 12-x Zr x O 19 , where x is 0.2-0.6 or BaFe 12-2x Zr x Co x O 19 , where x is 0.3-0.5. In some embodiments of the present invention, the doped barium ferrite may be, for example, BaFe 11.6 Zr0.4 O 19 ,BaFe 11 Co 0.5 Zr 0.5 O 19 or BaFe 11.2 Zr 0.4 Co 0.4 O 19 wait.

[0012] As a specific embodiment of the composite material described above in the present invention, the spiral carbon nanotube / doped barium ferrite composite material is a surfactant-modified spiral carbon nanotube / doped barium ferrite composite material.

[0013] As a specific embodiment of the composite material described above in the present invention, the mass ratio between the helical carbon nanotube / doped barium ferrite composite material and the surfactant is 1:2-1:3.

[0014] As a specific embodiment of the composite material described above of the present invention, the surfactant includes one or a combination of two of polyvinyl pyrrolidone and sodium dodecyl sulfate;

[0015] Sodium lauryl sulfate is preferred.

[0016] On the other hand, the present invention also provides a method for preparing the above-mentioned spiral carbon nanotube / doped barium ferrite composite material, wherein the preparation method comprises:

[0017] Step 1: according to the chemical formula of doped barium ferrite, an iron source, a barium source and a doped metal source are weighed and dissolved in deionized water to prepare a solution; a complexing agent is added to the solution to fully dissolve it, and then a pH regulator is added to allow the metal cations and the complexing agent to fully react with each other under stirring; spiral multi-walled carbon nanotubes are added to the solution obtained after the complexing reaction, and then heated and evaporated to dehydrate the solution to obtain a sol; the sol is calcined to obtain a spiral carbon nanotube / doped barium ferrite composite material powder;

[0018] Step 2: placing the spiral carbon nanotube / doped barium ferrite composite material powder in a solvent, stirring and dispersing it, filtering it, and then washing and drying the filter residue to obtain the spiral carbon nanotube / doped barium ferrite composite material.

[0019] As a specific embodiment of the preparation method described above of the present invention, the molar ratio of the complexing agent to the sum of all metal cations in the solution is 1.8-2.2:1;

[0020] Preferably, the complexing agent includes citric acid or the like.

[0021] As a specific embodiment of the preparation method described above of the present invention, a pH adjuster is added to adjust the pH value of the solution to 6-9;

[0022] Preferably, the pH adjuster includes ammonia water or the like.

[0023] As a specific embodiment of the above preparation method of the present invention, the heating evaporation temperature is 80-90° C. and the time is 24-48 hours.

[0024] As a specific embodiment of the preparation method described above of the present invention, the calcination comprises: heating to 400-500°C at a heating rate of 5-10°C / min for preheating for 1-3h; then heating to 1000-1200°C at a heating rate of 10-20°C / min under a protective gas atmosphere, calcining for 5-7h, and finally naturally cooling to room temperature;

[0025] Preferably, the protective gas atmosphere includes argon atmosphere or the like.

[0026] As a specific implementation of the above preparation method of the present invention, the mass ratio of the spiral multi-walled carbon nanotubes to the doped barium ferrite powder is 1:10-1:20.

[0027] As a specific embodiment of the above preparation method of the present invention, the preparation method further comprises:

[0028] Adding a surfactant to the solvent in step 2 and mixing well to obtain a surfactant solution with a concentration of 10-15 g / L;

[0029] The spiral carbon nanotube / doped barium ferrite composite material powder is placed in a surfactant solution, stirred and dispersed, and then filtered, and then the filter residue is washed and dried to obtain a surfactant-modified spiral carbon nanotube / doped barium ferrite composite material;

[0030] The mass ratio of the spiral carbon nanotube / doped barium ferrite composite material powder to the surfactant is 1:2-1:3.

[0031] As a specific embodiment of the preparation method described above in the present invention, in step 2, the solvent includes ethanol or deionized water.

[0032] As a specific embodiment of the preparation method described above of the present invention, in step 2, the stirring time is 1-6 hours.

[0033] As a specific embodiment of the preparation method described above of the present invention, in step 2, the drying temperature is 60-120° C. and the drying time is 6-24 h.

[0034] As a specific embodiment of the preparation method described above of the present invention, the surfactant includes one or a combination of two of polyvinyl pyrrolidone and sodium dodecyl sulfate;

[0035] Sodium lauryl sulfate is preferred.

[0036] In step 2 of the preparation method described above, filtration, washing and drying are all routine operations. Appropriate methods, materials and process parameters can be selected according to the actual situation on site for filtration, washing and drying, as long as the purpose of the present invention can be achieved.

[0037] On the other hand, the present invention also provides the use of the above-mentioned spiral carbon nanotube / doped barium ferrite composite material as an absorbing material in military equipment stealth, electronic equipment anti-electromagnetic interference, medical radiation protection or aerospace.

[0038] The spiral carbon nanotube / doped barium ferrite composite material provided by the present invention is obtained by compounding spiral multi-arm carbon nanotubes and doped barium ferrite, and has a fluffy mesh structure rich in microscopic cavities and conductive networks. The compounding of the spiral multi-arm carbon nanotubes and doped barium ferrite can optimize and adjust the electromagnetic parameters of the obtained composite material. Among them, the addition of doped barium ferrite can solve the skin effect and shielding effect of the spiral multi-arm carbon nanotubes, and the compounding of the spiral multi-arm carbon nanotubes can enhance the charge transfer ability and interface polarization ability of the doped barium ferrite. In addition to the screening of magnetic-dielectric components, that is, screening suitable spiral multi-arm carbon nanotubes and doped barium ferrites, the component ratio, interface characteristics and morphology structure (that is, the spiral multi-arm carbon nanotubes and doped barium ferrites are well overlapped by using surfactants without agglomeration, and the composite material has a fluffy porous network structure and a high specific surface area) also play an important role in the construction of binary porous network composite materials, that is, spiral carbon nanotubes / doped barium ferrite composite materials. Effective control of the above parameters can further improve the reflection loss intensity and absorption frequency of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1a XRD diagram of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material prepared in Test Example 1, Example 1, Example 2 and Comparative Example 1; Figure 1bThis is the XRD pattern of the sodium dodecyl sulfate modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material prepared in Example 5 in Test Example 1.

[0041] Figure 2a-2b They are SEM images of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material prepared in Comparative Example 1.

[0042] Figure 2c-2d They are SEM images of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material prepared in Example 2.

[0043] Figure 2e-2f They are SEM images of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material prepared in Example 1.

[0044] Figure 2g-2h They are TEM images of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material prepared in Example 1.

[0045] Figure 3 Magnetic hysteresis loops of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate prepared in Example 1, Example 2 and Comparative Example 1 in Test Example 3.

[0046] Figure 4a-4b Curves showing the variation of the real and imaginary parts of the dielectric constants of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite materials modified with sodium dodecyl sulfate obtained in Test Example 4, Example 1, Example 2 and Comparative Example 1 with respect to frequency.

[0047] Figure 4c-4d The curves showing the variation of the real and imaginary parts of the magnetic permeability of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite materials modified with sodium dodecyl sulfate obtained in Test Example 4, Example 1, Example 2 and Comparative Example 1 as a function of frequency are shown respectively.

[0048] Figure 4e-Figure 4g They are Fourier transform infrared spectra of the sodium dodecyl sulfate modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite materials prepared in Test Example 4, Example 1, Example 2 and Comparative Example 1, respectively.

[0049] Figure 5a-Figure 5b The attenuation coefficient and characteristic impedance of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate prepared in Test Example 5, Example 1, Example 2 and Comparative Example 1 are respectively changed with frequency.

[0050] Figure 5c-5dThey are respectively a three-dimensional model diagram and a two-dimensional plane diagram / two-dimensional contour diagram of the reflection loss of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate obtained in Example 1 in Test Example 5.

[0051] Figure 5e-5f They are respectively a three-dimensional model diagram and a two-dimensional plane diagram / two-dimensional contour diagram of the reflection loss of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate obtained in Example 2 in Test Example 5.

[0052] Figure 5g-Figure 5h They are respectively a three-dimensional model diagram and a two-dimensional plane diagram / two-dimensional contour diagram of the reflection loss of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate obtained in Comparative Example 1 in Test Example 5.

[0053] Figure 5i-5j They are respectively a three-dimensional model diagram and a two-dimensional plane diagram / two-dimensional contour diagram of the reflection loss of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate obtained in Example 5 in Test Example 5.

[0054] Figure 6a The UV-visible spectra of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite suspensions prepared in Example 1, Example 3, Example 4 and Comparative Example 2 in Test Example 6.

[0055] Figure 6b This is the UV-visible spectrum of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite suspension prepared in Example 6, Example 1, Comparative Example 3 and Comparative Example 4.

[0056] Figure 7a-7d They are BET isothermal adsorption curves of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite materials prepared in Test Example 7, Example 1, Example 3, Example 4 and Comparative Example 2, respectively.

[0057] Figure 7e-7f They are BET isothermal adsorption curves of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite materials modified with sodium dodecyl sulfate prepared in Test Example 7, Comparative Example 3 and Comparative Example 4, respectively.

[0058] Figure 8a-8b They are SEM images of the acidified helical multi-arm carbon nanotubes prepared in the preparation examples.

[0059] Figure 8c-Figure 8d They are TEM images of the acidified helical multi-arm carbon nanotubes prepared in the preparation examples. DETAILED DESCRIPTION

[0060] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0061] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0062] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0063] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0064] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0065] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0066] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0067] Preparation Example

[0068] This preparation example provides an acidified helical multi-arm carbon nanotube, which is prepared by a preparation method comprising the following specific steps:

[0069] First, acetylene (C 2 H 2 ) and hydrogen (H 2 ) as a raw material, and a magnetron sputtering method (PVD) is used to prepare spiral multi-arm carbon nanotubes, specifically comprising: uniformly dispersing a catalyst (PCl 3 The mass ratio of the combined catalyst and Ni is 1:2, that is, PCl is used in this preparation example. 3 The ceramic plate was placed in the PVD chamber and heated at a rate of 5°C / min under N 2 Heating to the synthesis temperature, i.e. 800°C in an environment;

[0070] After the temperature stabilizes, C 2 H 2 and H 2 The reaction was carried out at the synthesis temperature for 60 min, wherein C 2 H 2 and H 2 The gas flow rates of the PVD chamber were fixed at 5 mL / min and 10 mL / min, respectively. After the reaction was completed, the PVD chamber was placed under H 2 Cooling to room temperature in an environment to obtain spiral multi-arm carbon nanotubes;

[0071] Then, acidified spiral multi-arm carbon nanotubes are prepared, specifically comprising: adding concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3 into a beaker and mixing to obtain a mixed acid; taking more than 5 g of the prepared spiral multi-arm carbon nanotubes, adding them to 200 mL of the mixed acid, ultrasonically stirring for 3 hours, and maintaining a reaction temperature of 60° C. for acidification treatment; after the acidification treatment, separating the reactants by filtration with a vacuum pump, and repeatedly washing with deionized water until the pH value of the solution after rinsing is neutral; placing the product after the reaction into a drying oven for drying to obtain acidified spiral multi-arm carbon nanotubes, recorded as AHCNT.

[0072] The SEM image of AHCNT provided in this preparation example is as follows Figure 8a-8b As shown in the TEM image Figure 8c-Figure 8d As shown. Figure 8a-8b and Figure 8c-Figure 8d It can be seen that the AHCNTs are well formed, all curled in a regular and tight manner with a very short pitch of 50-100 nm, showing a symmetrical growth pattern.

[0073] Example 1

[0074] This embodiment provides a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0075] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0076] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0077] Add a certain amount of pH adjuster NH 3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0078] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0079] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and then the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0080] Add sodium dodecyl sulfate to 400 mL of ethanol to obtain a sodium dodecyl sulfate solution with a concentration of 10 g / L;

[0081] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a sodium dodecyl sulfate solution, and stirred in the sodium dodecyl sulfate solution for 6 hours using a magnetic stirrer. The product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0082] Example 2

[0083] This embodiment provides a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0084] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0085] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0086] Add a certain amount of pH adjuster NH 3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0087] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:10 to the doped barium ferrite;

[0088] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0089] Add sodium dodecyl sulfate to 400 mL of ethanol to obtain a sodium dodecyl sulfate solution with a concentration of 10 g / L;

[0090] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a sodium dodecyl sulfate solution, and stirred in the sodium dodecyl sulfate solution for 6 hours using a magnetic stirrer. The product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0091] Example 3

[0092] This embodiment provides a polyvinyl pyrrolidone-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0093] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0094] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0095] Add a certain amount of pH adjuster NH 3 ·H 2O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0096] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0097] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0098] Add polyvinyl pyrrolidone to 400 mL of ethanol to obtain a polyvinyl pyrrolidone solution with a concentration of 10 g / L;

[0099] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a polyvinyl pyrrolidone solution and stirred in the polyvinyl pyrrolidone solution for 6 hours using a magnetic stirrer. The product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol. The product was then vacuum dried at 80°C for 12 hours to obtain a polyvinyl pyrrolidone-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0100] Example 4

[0101] This embodiment provides an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0102] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0103] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0104] Add a certain amount of pH adjuster NH3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0105] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0106] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and then the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0107] 2 g of the sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to 400 mL of ethanol and stirred in the ethanol for 6 hours using a magnetic stirrer. The product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol. It was then vacuum dried at 80°C for 12 hours to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0108] Example 5

[0109] This embodiment provides a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0110] First, according to BaFe 11.2 Zr 0.4 Co 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、CoCl 2 6H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0111] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0112] Add a certain amount of pH adjuster NH3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0113] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0114] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and then the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0115] Add sodium dodecyl sulfate to 400 mL of ethanol to obtain a sodium dodecyl sulfate solution with a concentration of 10 g / L;

[0116] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a sodium dodecyl sulfate solution, and stirred in the sodium dodecyl sulfate solution for 6 hours using a magnetic stirrer. The product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0117] Comparative Example 1

[0118] This comparative example provides a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0119] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0120] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0121] Add a certain amount of pH adjuster NH 3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0122] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:8 to the doped barium ferrite;

[0123] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0124] Add sodium dodecyl sulfate to 400 mL of ethanol to obtain a sodium dodecyl sulfate solution with a concentration of 10 g / L;

[0125] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a sodium dodecyl sulfate solution, and stirred in the sodium dodecyl sulfate solution for 6 hours using a magnetic stirrer. The product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0126] Comparative Example 2

[0127] This comparative example provides a hexadecyltrimethylammonium bromide-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0128] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0129] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0130] Add a certain amount of pH adjuster NH 3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0131] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0132] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0133] Adding cetyltrimethylammonium bromide to 400 mL of ethanol to obtain a cetyltrimethylammonium bromide solution having a concentration of 10 g / L;

[0134] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a hexadecyltrimethylammonium bromide solution, stirred in the hexadecyltrimethylammonium bromide solution for 6 hours using a magnetic stirrer, and then the product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a hexadecyltrimethylammonium bromide-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0135] Comparative Example 3

[0136] This comparative example provides a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0137] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0138] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0139] Add a certain amount of pH adjuster NH 3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0140] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0141] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and then the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0142] Add sodium dodecyl sulfate to 400 mL of ethanol to obtain a sodium dodecyl sulfate solution with a concentration of 5 g / L;

[0143] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a sodium dodecyl sulfate solution, stirred in the sodium dodecyl sulfate solution for 6 hours using a magnetic stirrer, and then the product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0144] Comparative Example 4

[0145] This comparative example provides a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material, which is prepared by a preparation method comprising the following specific steps:

[0146] First, according to BaFe 11.6 Zr 0.4 O 19 Chemical formula, weigh FeC1 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3) 4 ·5H 2 O, and dissolve it in 400 mL of deionized water to obtain a precursor solution;

[0147] At the same time, a certain amount of citric acid is weighed and dissolved in the precursor solution, and the molar ratio of citric acid to all metal cations is 2:1;

[0148] Add a certain amount of pH adjuster NH 3 ·H 2 O, make the pH value of the solution reach 8, use a magnetic stirrer to quickly stir the solution to make it fully mixed and react for a certain time;

[0149] After the predetermined time is reached, the acidified spiral multi-arm carbon nanotubes prepared in the preparation example are added to the solution in a mass ratio of 1:12 to the doped barium ferrite;

[0150] After the predetermined time is reached, the mixed solution is heated and evaporated for 36 hours at 88° C. to dehydrate the mixed solution to obtain a sol, and then the sol is placed in a muffle furnace, heated to 450° C. at a rate of 5° C. / min, and preheated at this temperature for 2 hours, and then heated to 1200° C. at a heating rate of 10° C. / min under a protective gas, such as an argon atmosphere, and calcined for 5 hours, and then naturally cooled to room temperature to obtain an acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder;

[0151] Add sodium dodecyl sulfate to 400 mL of ethanol to obtain a sodium dodecyl sulfate solution with a concentration of 20 g / L;

[0152] 2 g of sintered acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material powder was added to a sodium dodecyl sulfate solution, stirred in the sodium dodecyl sulfate solution for 6 hours using a magnetic stirrer, and then the product was filtered, and the filter residue was washed with deionized water and anhydrous ethanol, and then vacuum dried at 80°C for 12 hours to obtain a sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material.

[0153] Test Example 1

[0154] In this test example, XRD analysis was performed on the sodium dodecyl sulfate modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material obtained in Example 1, Example 2, Example 5 and Comparative Example 1, wherein the XRD spectra of the composite material obtained in Example 1, Example 2 and Comparative Example 1 are as follows: Figure 1a As shown, from Figure 1aIt can be seen that each group of samples has characteristic peaks of M-type barium ferrite at 30.3°, 30.8°, etc., which match (JCPDS27-1029). In addition, a broad diffraction peak corresponding to the (002) crystal plane of carbon nanotubes appears at 26.3°, which confirms the presence of M-type barium ferrite and carbon nanotubes in the composite material.

[0155] The XRD spectrum of the composite material obtained in Example 5 is as follows: Figure 1b As shown, from Figure 1b The characteristic peaks of M-type barium ferrite and carbon nanotubes can be found, which indicates that the use of BaFe 11.2 Zr 0.4 Co 0.4 O 19 A well-formed acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material can also be prepared by compounding it with acidified spiral multi-arm carbon nanotubes as a magnetic component.

[0156] Test Example 2

[0157] In this test example, SEM analysis was performed on the sodium dodecyl sulfate modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material obtained in Example 1, Example 2 and Comparative Example 1. The experimental results are shown as follows: Figure 2a-2f As shown. Among them, Figure 2a-2b The SEM image of the composite material provided for Comparative Example 1, Figure 2c-2d The SEM image of the composite material provided in Example 2 and Figure 2e-2f This is a SEM image of the composite material provided in Example 1. As can be seen from the above figure, the doped barium ferrite powder still grows in a flake state, and the size of the adhered powder is larger than that of the free powder as a whole; and as the content of the acidified spiral multi-walled carbon nanotubes increases, they continue to adhere to the surface of the doped barium ferrite particles and the gaps, and their abundant active sites are well overlapped with the magnetic components, and then the doped barium ferrite sheets and the spiral multi-walled carbon nanotubes overlap with each other in a tube-sheet structure, forming a fluffy conductive network structure rich in microscopic cavities.

[0158] This test example also carried out TEM analysis on the sodium dodecyl sulfate modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material obtained in Example 1. The obtained TEM images are as follows: Figure 2g-2h As shown in the figure, it can be seen that the doped barium ferrite sheet is closely attached to the acidified spiral multi-walled carbon nanotube. Figure 2a As shown in the results in the dotted box, there are multiple acidified spiral multi-walled carbon nanotubes in the composite material provided in Comparative Example 1 that are locally aggregated and entangled with each other. This is because there is an excess of acidified spiral multi-walled carbon nanotubes in Comparative Example 1. For nanoscale materials, they have a higher van der Waals force, and excess or poor dispersion will cause agglomeration.

[0159] Test Example 3

[0160] This test example examines the static magnetic parameters of the acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material modified with sodium dodecyl sulfate obtained in Example 1, Example 2 and Comparative Example 1. The obtained hysteresis loop is as follows: Figure 3 As shown. Figure 3 It can be seen that with the increase in the mass ratio of acidified spiral multi-walled carbon nanotubes, the saturation magnetization and coercive force of the composite material are slightly reduced. The saturation magnetization and coercive force of the composite materials provided in Example 1 and Example 2 are 112.70emm / g, 103.63emm / g and 1624.30Oe, 1602.45Oe, respectively, while the saturation magnetization and coercive force of the composite material provided in Comparative Example 1 are reduced to 85.80emm / g and 1589.32Oe. This shows that the addition of excessive acidified spiral multi-walled carbon nanotubes will reduce the magnetism of the composite material. On the one hand, the addition of excessive acidified spiral multi-walled carbon nanotubes will produce agglomeration and change the structure of the composite material; on the other hand, acidified spiral multi-walled carbon nanotubes are a non-magnetic substance, and the addition of excessive acidified spiral carbon nanotubes will significantly reduce the overall magnetism of the composite material.

[0161] Test Example 4

[0162] This test example examines the electromagnetic parameters of the sodium dodecyl sulfate-modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite materials prepared in Example 1, Example 2 and Comparative Example 1, respectively. Figure 4a and Figure 4b The real and imaginary parts of the dielectric constants of the composite materials obtained in Example 1, Example 2 and Comparative Example 1 are respectively the curves of the change of the real and imaginary parts of the dielectric constants with the frequency. Figure 4a and Figure 4b It can be seen that the real part of the dielectric constant of the composite materials obtained in Example 1, Example 2 and Comparative Example 1 shows obvious dispersion characteristics, and the imaginary part changes with frequency fluctuations, producing bumps at 27, 32, 35, 37 GHz, etc., which indicates that the composite materials with different mass ratios of acidified spiral multi-arm carbon nanotubes and doped barium ferrite have similar dielectric loss mechanisms.

[0163] In addition, this test example also carried out infrared spectroscopy analysis on the composite materials obtained in Example 1, Example 2 and Comparative Example 1, and the obtained infrared spectra were as follows: Figure 4e , Figure 4f and Figure 4g As shown. Figure 4e , Figure 4f and Figure 4gIt can be seen that the composite materials obtained in Example 1, Example 2 and Comparative Example 1 all have multiple functional groups and unsaturated bonds, and have more polarized dipoles. At the same time, as a nanoporous material, it also has multiple electromagnetic wave scattering surfaces. In summary, since the composite material has more heterojunction interfaces, microscopic voids and dipole pairs, it will produce obvious space charge polarization, dipole steering polarization and electromagnetic wave multiple scattering, and has strong dielectric relaxation and conductive loss capabilities.

[0164] Figure 4c and Figure 4d The real and imaginary parts of the magnetic permeability of the composite materials obtained in Example 1, Example 2 and Comparative Example 1 are respectively the curves of the variation of the real and imaginary parts of the magnetic permeability with the frequency. Figure 4c and Figure 4d It can be seen that the real and imaginary curves of the composite materials obtained in Example 1, Example 2 and Comparative Example 1 have similar changes. The real part fluctuates downward as the frequency increases, and the imaginary part has peaks and troughs, and the corresponding frequencies are close. The imaginary part of the composite material provided in Comparative Example 1 has significantly decreased in permeability, which is only 1 / 3 of the composite material provided in Example 1. This is because: first, the acidified spiral multi-walled carbon nanotubes are non-magnetic materials, and excessive addition will weaken the dipole interaction; secondly, the addition of acidified spiral multi-walled carbon nanotubes will cause drastic changes in the structure of the composite material, thereby making the imaginary part of the permeability change trend gentle; finally, too much carbon-based material can generate strong microcurrents at high frequencies, produce obvious anti-magnetism, and weaken the expression of the material's magnetic properties.

[0165] Test Example 5

[0166] This test example examines the electromagnetic attenuation, impedance matching and wave absorption performance of the sodium dodecyl sulfate modified acidified spiral multi-arm carbon nanotube / doped barium ferrite composite material obtained in Example 1, Example 2, Example 5 and Comparative Example 1. The attenuation coefficient and characteristic impedance of the composite material obtained in Example 1, Example 2 and Comparative Example 1 are shown in the curves of frequency change. Figure 5a and Figure 5bAs shown. Combined with the loss angle analysis, it can be seen that the attenuation capacity of the composite materials provided in Example 1 and Example 2 is significantly higher than that of Comparative Example 1, and the overall attenuation capacity of the composite material provided in Example 1 is the strongest. At the same time, the composite materials provided in Example 1 and Example 2 have higher characteristic impedance and better impedance matching performance, which is related to their better magnetic loss performance and the smaller difference between dielectric constant and magnetic permeability. The impedance matching characteristics of the composite material provided in Comparative Example 1 are also significantly weaker than those of the composite materials provided in Example 1 and Example 2. This is because: first, the acidified spiral multi-arm carbon nanotubes are non-magnetic materials, and excessive addition will weaken the dipole interaction; secondly, the addition of acidified spiral multi-arm carbon nanotubes will cause drastic changes in the structure of the composite material, thereby making the imaginary part of the magnetic permeability change trend smooth; finally, too much carbon-based material can generate strong microcurrents at high frequencies, resulting in obvious anti-magnetism, thereby weakening the magnetic performance expression of the composite material.

[0167] Figure 5c-5h The three-dimensional model diagram and two-dimensional plane diagram / two-dimensional contour diagram of the reflection loss of the composite materials obtained in Example 1, Example 2 and Comparative Example 1 are shown respectively. It can be seen from these figures that in terms of minimum reflection loss, the composite material provided in Example 1 performs best, reaching -50.22dB at 26.7GHz, and the matching thickness at this time is 2.80mm; in terms of effective wave absorption band, the composite material provided in Example 2 has the widest wave absorption band when the matching thickness is 2.52mm, and its effective wave absorption bandwidth is as high as 11.65GHz, almost covering the entire Ka band. Therefore, the wave absorption performance of the composite materials provided in Examples 1 and 2 is significantly higher than that of the composite material provided in Comparative Example 1, because: the gap between the dielectric constant and the magnetic permeability increases after the acidified spiral multi-arm carbon nanotubes are compounded with the barium-doped ferrite, weakening the impedance matching and weakening the magnetic loss performance, and the excessive addition of acidified spiral multi-arm carbon nanotubes in Comparative Example 1 causes agglomeration and mutual entanglement, which is not conducive to electromagnetic synergistic loss, thereby affecting the effective absorption bandwidth and reflection loss of the material. Nevertheless, because the acidified spiral multi-arm carbon nanotubes have strong dielectric loss capacity, their combination with doped barium ferrite brings richer interfaces and microcavity structures, which is conducive to multiple scattering of electromagnetic waves. Within the appropriate addition range, the preparation of lightweight electromagnetic wave absorbing materials can be achieved.

[0168] Figure 5i-5j The three-dimensional model diagram and two-dimensional plane diagram / two-dimensional contour diagram of the reflection loss of the composite material obtained in Example 5 are shown in FIG. Figure 5i-5j It can be seen that the minimum reflection loss of the composite material provided in Example 5 is -50.32 dB, and the effective absorption bandwidth is 12.76 GHz, which shows that under the appropriate ratio and surface activation treatment, the use of BaFe 11.2 Zr 0.4 Co 0.4 O19 The composite material prepared by combining the magnetic component with acidified helical multi-arm carbon nanotubes also has good microwave absorption performance.

[0169] Test Example 6

[0170] In this test example, Zeta potential and UV-visible spectroscopy were used to test the reflectivity and stability of the dispersed solution system obtained in step 2 of Example 1, Example 3, Example 4, Comparative Example 2, Comparative Example 3 and Comparative Example 4 (i.e., the mixed solution obtained after 6 hours of stirring in the examples and comparative examples). The test results are shown in Tables 1 and 2. Figure 6a-Figure 6b shown.

[0171] Table 1 Zeta potential under different surfactants

[0172]

[0173]

[0174] As can be seen from Table 1 above, the average Zeta potential of the dispersed solution systems in Example 1, Example 3, Comparative Example 4 and Comparative Example 2 are -56.2mV, -44.3mV, -25.2mV and -22.6mV respectively. It is generally believed that the absolute value of the Zeta potential of nanoparticles exceeding 30mV can be stably dispersed. It can be seen that the average Zeta potential of the sodium dodecyl sulfate dispersed solution system in Example 1 is the best, the polyvinyl pyrrolidone (PVP) in Example 3 is second, and the hexadecyl trimethyl ammonium bromide in Comparative Example 2 is the worst, even worse than the dispersed solution system without adding surfactant in Example 4. This is because: PVP and sodium dodecyl sulfate are both amphiphilic substances, which can be well coated and adsorbed on the particle surface, reduce surface tension, and promote the stability and dispersion of the system. However, PVP is a nonionic surfactant, and sodium dodecyl sulfate is an anionic surfactant. Therefore, sodium dodecyl sulfate can ionize more anions, promote the negative charge on the surface of the acidified spiral multi-walled carbon nanotubes, and increase electrostatic repulsion. Although hexadecyltrimethylammonium bromide is also a surfactant dispersant, it is a cationic surfactant, which is not conducive to increasing the electrostatic repulsion of particles and has a low adsorption effect on materials.

[0175] The stability of the dispersed system is positively correlated with the absorbance. Figure 6a The UV-visible spectra of the composite materials provided in Example 1, Example 3, Example 4 and Comparative Example 2 are shown in FIG. Figure 6aIt can be seen that the UV-visible spectrum change curves of each group of composite materials are similar, and the frequency bands corresponding to the maximum absorbance are close, all around 210nm. The maximum absorbances of the composite materials provided by Example 1, Example 3, Example 4 and Comparative Example 2 are 6.12, 5.98, 4.21, and 3.35, respectively. It can be seen that the sodium dodecyl sulfate used in Example 1 has the best stability, the PVP used in Example 3 has the second best stability, and the hexadecyl trimethyl ammonium bromide used in Comparative Example 3 has poor stability, even worse than the case where no surfactant is used in Example 4.

[0176] Figure 6b The UV-visible spectra of the composite materials provided in Example 1, Comparative Example 3 and Comparative Example 4 are shown in FIG. Figure 6b It can be seen that the spectrophotometry of the composite materials provided by Example 1, Comparative Example 3 and Comparative Example 4 corresponds to 6.12, 5.62 and 3.72 respectively. It can be seen that with the increase in the amount of sodium dodecyl sulfate added, the stability of the system first increases and then weakens. This is because: in the initial stage, with the increase in the content of surfactant, the increase in spatial repulsion potential energy and electrostatic repulsion potential energy and the weakening effect of the Hamaker constant are enhanced, thereby increasing the total potential energy of the system, which is conducive to the dispersion of the material; but when an excess of surfactant is added, some surfactants cannot be well adsorbed on the surface of the composite material, thereby generating negative adsorption, forming a vacancy layer, increasing the gravitational potential energy, and being unfavorable for the dispersion of the composite material.

[0177] Test Example 7

[0178] This test example uses the BET specific surface area test method to test the specific surface area of ​​the composite materials provided in Example 1, Example 3, Example 4, Comparative Example 2, Comparative Example 3 and Comparative Example 4. Among them, the isothermal adsorption curves of the composite materials provided in Example 1, Example 3, Example 4 and Comparative Example 2 are respectively as follows: Figure 7a-7d As shown. Figure 7a-7d It can be found that the curves of each group of composite materials belong to type II isotherms, indicating that they have similar adsorption mechanisms. The specific surface areas of the composite materials provided by Example 1, Example 3, Example 4, and Comparative Example 2 are calculated by fitting, and are 516.09 m 2 / g, 473.67m 2 / g, 394.81m 2 / g and 302.42m 2 / g. It can be seen that the specific surface area of ​​the composite material provided by Example 1 is the largest, followed by Example 3, and Comparative Example 2 is the worst and inferior to Example 4 without using any surfactant, and the composite materials provided by Example 1 and Example 3 have more pores, indicating that the dispersion uniformity of doped barium ferrite and acidified spiral multi-walled carbon nanotubes is better. This is because: sodium dodecyl sulfate belongs to anionic amphiphilic compounds, which have dodecyl chain hydrophobic groups and ether sulfonic acid hydrophilic groups, can be well adsorbed on the surface of the composite material and improve the uniformity of material dispersion, and as an anionic dispersant, it can increase the Stern potential of the particles and increase the repulsive potential energy between the particles. At the same time, it also has a longer alkyl chain, which can generate structural entropy repulsive potential energy and elastic repulsive potential energy when the particles agglomerate, thereby generating a steric hindrance. In addition, sodium dodecyl sulfate attached to the surface of the particles will reduce the Hamaker constant and weaken the gravitational potential energy that makes the particles aggregate. As a polymer, PVP has a longer carbon chain and is also amphiphilic. It can adsorb on the surface of materials to form a PVP film, reduce the interfacial tension on the surface of materials, increase the spatial repulsive potential energy, weaken the van der Waals force between particles, and help disperse particles. As a cationic surfactant, hexadecyltrimethylammonium bromide can also reduce the interfacial tension of materials, but it is not conducive to the increase of repulsive potential energy, resulting in poor dispersion effect.

[0179] Figure 7a , Figure 7e and Figure 7f The isothermal adsorption curves of the composite materials provided in Example 1, Comparative Example 3 and Comparative Example 4 are shown respectively. Figure 7a , Figure 7e and Figure 7f It can be seen that these treated composite materials also belong to type II isotherms. After fitting calculation, the specific surface areas of the composite materials provided by Example 1, Comparative Example 3 and Comparative Example 4 are 516.09 m 2 / g,456.58m 2 / g,404.42m 2 / g. It can be seen that compared with the composite materials provided in Comparative Examples 3 and 4, the composite material provided in Example 1 has a larger specific surface area, more pores, and better dispersion uniformity. This shows that when the addition amount of sodium dodecyl sulfate reaches a certain value, its spatial repulsion potential energy and electrostatic repulsion potential energy increase effect and Hamaker constant weakening effect are obvious, which is conducive to material dispersion, but when sodium dodecyl sulfate is added in excess, vacancy effect is generated, which is not conducive to the dispersion of the composite material.

[0180] In summary, the mass ratio of the acidified spiral multi-walled carbon nanotubes and the doped barium ferrite in the composite material provided in Comparative Example 1 is relatively high, the composite material provided in Example 4 is not dispersed using a surfactant, the composite material provided in Comparative Example 2 is dispersed using hexadecyltrimethylammonium bromide, the composite material provided in Comparative Example 3 uses a lower surfactant content, and the composite material provided in Comparative Example 4 uses a higher surfactant content. It can be seen from the above figures and Table 1 that due to the unreasonable mass ratio of the acidified spiral multi-walled carbon nanotubes and the doped barium ferrite, the electromagnetic properties inside the composite material system will not match, thereby making the magnetic permeability, saturation magnetization and coercive force of the composite material provided in Comparative Example 1 smaller, the loss capacity and impedance matching characteristics are lower, and the wave absorption performance is weaker; due to the unreasonable surfactant addition method, the repulsive force between the particles cannot be effectively regulated, thereby making the charge repulsion between the particles of the composite materials provided in Example 4 and Comparative Examples 2-Comparative Example 4 smaller, the suspension stability is lower, the powder dispersibility is weaker, and the specific surface area is smaller.

[0181] From the experimental data in the above test examples, it can be seen that the embodiment of the present invention uses FeCl 3 6H 2 O、BaCl 2 ·2H 2 O、Zr(NO 3 ) 4 ·5H 2 O and acidified spiral multi-arm carbon nanotubes as raw materials, by changing the mass ratio of acidified spiral multi-walled carbon nanotubes to doped barium ferrite, the type and content of surfactant, surfactant-modified or non-surfactant-modified acidified spiral multi-arm carbon nanotubes / doped barium ferrite composite absorbing materials with different electromagnetic properties were prepared.

[0182] Facts have proved that the composite material prepared by the embodiment of the present invention does not have an obvious impurity phase, realizes the effective overlap between the doped barium ferrite sheet and the acidified spiral multi-walled carbon nanotube in a tube-sheet structure, and while having a high specific surface area and dielectric constant, the composite material has good saturation magnetization intensity, magnetic permeability, electromagnetic attenuation coefficient and impedance matching characteristics, so that it exhibits excellent comprehensive wave absorbing performance; and when modified with a sodium dodecyl sulfate ethanol solution with a concentration of 10 g / L and the mass ratio of the acidified spiral multi-walled carbon nanotube to the doped barium ferrite is controlled to be 1:12, the specific surface area and reflection loss of the composite material obtained by the embodiment of the present invention are optimal.

[0183] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A spiral carbon nanotube / doped barium ferrite composite material, characterized in that: The spiral carbon nanotube / doped barium ferrite composite material is a fluffy mesh structure rich in microscopic cavities and conductive networks, including doped barium ferrite and spiral multi-walled carbon nanotubes. The doped barium ferrite is a doped barium ferrite sheet formed by the sheet-like growth of doped barium ferrite particles. The spiral multi-walled carbon nanotubes are attached to the surface and gaps of the doped barium ferrite particles. The active sites of the spiral multi-walled carbon nanotubes overlap with the doped barium ferrite, and then the doped barium ferrite sheets and the spiral multi-walled carbon nanotubes overlap with each other in a tube-sheet structure.

2. The composite material according to claim 1, characterized in that The mass ratio of the spiral multi-walled carbon nanotubes to the doped barium ferrite is 1:10-1:20; Also preferably, the spiral multi-walled carbon nanotubes are acidified spiral multi-walled carbon nanotubes; Also preferably, the doped barium ferrite comprises BaFe 12-x Zr x O 19 , where x is 0.2-0.6 or BaFe 12- 2x Zr x Co x O 19 , where x is 0.3-0.

5.

3. The composite material according to claim 1 or 2, characterized in that: The spiral carbon nanotube / doped barium ferrite composite material is a surfactant-modified spiral carbon nanotube / doped barium ferrite composite material; Preferably, the mass ratio between the helical carbon nanotube / doped barium ferrite composite material and the surfactant is 1:2-1:3; Also preferably, the surfactant comprises one or a combination of polyvinyl pyrrolidone and sodium lauryl sulfate; more preferably sodium lauryl sulfate.

4. The method for preparing the helical carbon nanotube / doped barium ferrite composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step 1: according to the chemical formula of doped barium ferrite, an iron source, a barium source and a doped metal source are weighed and dissolved in deionized water to prepare a solution; a complexing agent is added to the solution to fully dissolve it, and then a pH regulator is added to allow the metal cations and the complexing agent to fully react with each other under stirring; spiral multi-walled carbon nanotubes are added to the solution obtained after the complexing reaction, and then heated and evaporated to dehydrate the solution to obtain a sol; the sol is calcined to obtain a spiral carbon nanotube / doped barium ferrite composite material powder; Step 2: placing the spiral carbon nanotube / doped barium ferrite composite material powder in a solvent, stirring and dispersing it, filtering it, and then washing and drying the filter residue to obtain the spiral carbon nanotube / doped barium ferrite composite material.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the complexing agent to the sum of all metal cations in the solution is 1.8-2.2:1; Preferably, the complexing agent comprises citric acid.

6. The preparation method according to claim 4 or 5, characterized in that: Add a pH adjuster to adjust the pH value of the solution to 6-9; Preferably, the pH adjuster comprises aqueous ammonia.

7. The preparation method according to claim 4 or 5, characterized in that: The heating evaporation temperature is 80-90°C and the time is 24-48h; Preferably, the calcination comprises: heating to 400-500°C at a heating rate of 5-10°C / min for preheating for 1-3h; then heating to 1000-1200°C at a heating rate of 10-20°C / min under a protective gas atmosphere, calcining for 5-7h, and finally naturally cooling to room temperature; More preferably, the protective gas atmosphere comprises an argon atmosphere.

8. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the spiral multi-walled carbon nanotubes to the doped barium ferrite powder is 1:10-1:

20.

9. The preparation method according to claim 4 or 5, characterized in that: The preparation method further comprises: Adding a surfactant to the solvent in step 2 and mixing well to obtain a surfactant solution with a concentration of 10-15 g / L; The spiral carbon nanotube / doped barium ferrite composite material powder is placed in a surfactant solution, stirred and dispersed, and then filtered, and then the filter residue is washed and dried to obtain a surfactant-modified spiral carbon nanotube / doped barium ferrite composite material; Wherein, the mass ratio between the helical carbon nanotube / doped barium ferrite composite material powder and the surfactant is 1:2-1:3; Preferably, in step 2, the solvent includes ethanol or deionized water; Also preferably, in step 2, the stirring time is 1-6h; Also preferably, in step 2, the drying temperature is 60-120° C. and the drying time is 6-24 h; Also preferably, the surfactant includes one or a combination of polyvinyl pyrrolidone and sodium lauryl sulfate; more preferably sodium lauryl sulfate.

10. Application of the spiral carbon nanotube / doped barium ferrite composite material according to any one of claims 1 to 3 as an absorbing material in military equipment stealth, electronic equipment anti-electromagnetic interference, medical radiation protection or aerospace.

Citation Information

Cited By

  • Doped barium ferrite carbon nanotube coating type wave-absorbing material and preparation method thereof

    CN121851848A